Integrated Planning of Thematic Green Open Spaces with Goals of Urban Detailed Spatial Planning - Fran Sinatra; Adsari Monalisa; Mohammad Solehin Fitry bin Rosley; Muhammad Irfan Affandi; Abdul Mubdi Bindar (Faculty of Engineering, Andi Djemma University, 2024)
This research aims to generate the theme of urban parks by developing urban areas towards livable cities. Qualitative and quantitative descriptive methods are operated to identify the availability of urban parks, discover the characteristics of urban development areas, and arrange the theme of a park. Eight themes could be adopted: history and culture, entertainment, hobbies, health, conservation, hazard mitigation, branding, and education. The objective of urban development areas, structure plan, land use, and specific characteristics of an area are considered when selecting the theme of the urban parks. As a primer area in development, WP I has more variety in urban park themes than the others.